LEGISLATION AND COMPARATIVE LAW UNDER THE GOVERNMENT OF THE RUSSIAN FEDERATION - Kashirkina , Анна Анатольевна; Morozov, Андрей Николаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The Treaty on the Eurasian economic Union, signed by the heads of state of the Republic of Belarus, Republic of Kazakhstan and the Russian Federation on may 29, 2014, entered into force on 1 January 2015 This Agreement transformed the pre-existing Customs Union in new interstate integration - the Eurasian economic Union. Thus, the Eurasian integration goes through certain stages of economic and political development. Consequently, we can speak about the formation of the Eurasian integration. Each formation of Eurasian integration has its historical background, international legal characteristics and specificity for member States.